We cannot see the triangle
Answer:
the 3rd one
Step-by-step explanation:
i just know
IF UR USERNAME IS A JOKE F U. if its not then i support you
Complete question:
y = 2x² + 2x - 3
x = -2 -1 0 1 2
Answer:
<u>Complete table of values</u>
x: -2 -1 0 1 2
y: 1 -3 -3 1 9
Step-by-step explanation:
Given;
y = 2x² + 2x - 3
To complete the table of values of the equation above, we substitute the value of x into the given equation and solve for y.
when, x = -2
y = 2(-2)² + 2(-2) - 3
y = 8 - 4 - 3
y = 1
when x = -1
y = 2(-1)² + 2(-1) - 3
y = 2 - 2 - 3
y = -3
when x = 0
y = 2(0)² + 2(0) - 3
y = 0 - 0 - 3
y = -3
when x = 1
y = 2(1)² + 2(1) - 3
y = 2 + 2 - 3
y = 1
when x = 2
y = 2(2)² + 2(2) - 3
y = 8 + 4 - 3
y = 9
<u>Complete table</u>
x: -2 -1 0 1 2
y: 1 -3 -3 1 9
That person, the someone, would have the 5 that they stole
hope this helps ;)
Answer:
3 x + 14
Step-by-step explanation:
Simplify the following:
6 x - 3 x - 11 + 25
Grouping like terms, 6 x - 3 x - 11 + 25 = (6 x - 3 x) + (-11 + 25):
(6 x - 3 x) + (-11 + 25)
6 x - 3 x = 3 x:
3 x + (-11 + 25)
25 - 11 = 14:
Answer: 3 x + 14